LANGUAGE BARRIERS OF INTERNATIONAL STUDENTS IN INDONESIA: FORMS AND CONTRIBUTING FACTORS - Fendy Yogha Pratama; Ali Mohammed Saleh Al-Hamzi; Febi Junaidi; Rokayah Luebaesa (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
Language barriers play a crucial role in shaping international students’ academic success and social adjustment. However, limited research has examined how these barriers are experienced in the Indonesian context. This study examines the forms and contributing factors of language barriers experienced by 11 Thai international students in Indonesia as part of their academic adjustment. Combination of in-depth interviews and focus group discussions were used in the data collection procedure. The findings reveal that the students encountered difficulties in listening comprehension, speaking anxiety, grammar mastery, and reading academic texts. Contributing factors included fear of peer judgment, limited vocabulary, accent variation, and lack of familiarity with the topics. The study concludes that language barriers are not limited to lingustic aspects but also involve psychological and social dimensions. It highlights the urgency for Indonesian higher institutions to implement tailored language support, inclusive pedagogy, and academic services to foster international students’ effective adjusment.